2020
DOI: 10.3389/fmicb.2020.00166
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Stability of Composite SCCmec ACME and COMER-Like Genetic Elements in Staphylococcus epidermidis Correlates With Rate of Excision

Abstract: The epidemiological success of methicillin-resistant Staphylococcus aureus USA300 has been associated with the presence of two mobile elements, the arginine catabolic mobile element (ACME) and the copper and mercury resistance (COMER) element. These two mobile elements are associated with resistance to copper, which has been related to host fitness and survival within macrophages. Several studies found that ACME is more prevalent, and exhibits greater diversity, in Staphylococcus epidermidis while COMER has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
6
16
0
Order By: Relevance
“…A similar destabilization of the virulence plasmid in the FS-1 treated E. coli BAA-196 was reported in a previous publication (Korotetskiy et al, 2020b). The varying rate of excision of SCCmec cassettes from Staphylococcal populations was reported in another publication (Almebairik et al, 2020). However, it should be noted that in the current work, the rate of SCCmec excision in NC and FS cultures was not measured.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar destabilization of the virulence plasmid in the FS-1 treated E. coli BAA-196 was reported in a previous publication (Korotetskiy et al, 2020b). The varying rate of excision of SCCmec cassettes from Staphylococcal populations was reported in another publication (Almebairik et al, 2020). However, it should be noted that in the current work, the rate of SCCmec excision in NC and FS cultures was not measured.…”
Section: Discussionsupporting
confidence: 87%
“…The staphylococcal methicillinresistance chromosome cassette (SCCmec), comprising mecA and mecR genes (Holden et al, 2004;Jani et al, 2017), was found in both genomes ∼50 kbp downstream from the replication origin. However, the coverage of PacBio reads overlapping the SCCmec region decreased significantly in both NC and FS genomes, indicating that this mobile element could be unstable in the culture and that there was a tendency to drop this element when S. aureus was cultivated without the selective pressure of the antibiotic that is in agreement with previously published reports (Stojanov et al, 2015;Almebairik et al, 2020). This may explain the fact that both NC and FS cultures gained sensitivity to methicillin after 10 passages of cultivation on the media without the antibiotic (Table 1).…”
Section: Complete Genome Assemblysupporting
confidence: 91%
See 1 more Smart Citation
“…While in HD29 only an ACME type V-associated fragment containing the ars -operon and a putative functional CRISPR-Cas system was deleted in INF isolates. This shows that rearrangements occur relatively often in the region of SCC mec and ACME compared to other regions ( S10 Table ), as has been observed in vitro [ 55 57 ]. Interestingly, deletions in these regions seem to occur preferentially in infection, while integrity is maintained in the nose.…”
Section: Resultssupporting
confidence: 69%
“…These rearrangements indicate the high genomic plasticity of S. epidermidis particularly in the SCCmec and ACME region compared to other regions. This observation has also been noted in in vitro studies where ACME have highly variable structures with 100 times higher excision frequency found for the SCCmec elements [3,19].…”
Section: Sccmec and Acme Typessupporting
confidence: 72%